Pengaruh Senam Hipertensi Terhadap Tekanan Darah Lansia Di RW 02 Kelurahan Keroncong - Siti Robeatul Adawiyah; Marki Marki; Lis Nuraisyah; Abdillah Kurni P; Alif Wisageni; Aef Eka S; Benget Cris D.A; Cut Eka P; Dewi Sumiati; Eli Mantika; Fauzi Iskandar; Imam Saguh M; Johanes Parasian; Khaerul Anwar; Laily Maftuhah; Latifah Maulina; Repidawati Sinaga; Restika Muji C; Rita Dona M; Umi Salamah (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
The elderly are an age group of humans who have entered the final stage of their life phase. With increasing age, physiological functions decrease due to the aging process so many non-communicable diseases appear in the elderly, one of the diseases that often occurs in the elderly community is hypertension. Hypertension is a vascular disorder characterized by systolic blood pressure equal to or above 140 mmHg, and or diastolic blood pressure equal to or above 90 mmHg. Community nursing is the practice of maintaining and improving public health by using knowledge from nursing science. In this community service, one way to maintain and improve public health is by providing hypertension health education and hypertension gymnastics that aim to control blood pressure.